DEVELOPMENT OF CUSTOMER RELATIONSHIP MANAGEMENT SYSTEM TO IMPROVE SERVICE QUALITY IN PT MANULIFE LIFE INSURANCE INDONESIA - Chriswanto, Chriswanto (CommIT (Communication and Information Technology) Journal, 2014)
Customer Relationship Management System (CRMS) Development in order to improve service quality in PT. AJ. Manulife Indonesia is done by comprehending the performance model of the company and the factors that are affecting the company performance improvement and the quality of the decision to be taken by top management. System Dynamic is a method that can be used to stimulate complex systems. System Dynamics approach is expected to build a model of corporate performance that can be used to evaluate the quality of service to customers so that they can make decisions quickly and accurately. This study proves that the model is built with standard models used as changing targets and it can simulate a target quality of service to customers by delivering current and future achievement. Achievement in the future is influenced by the value of achievement of SLA, Response Time, and Defect, where the greater value of control, the greater value of the correction rate so that the GAP will be smaller. Correction rate which is determined in this study was 10%, 20%, and 30% of GAP (CB)